Problemas de máximo e mínimo na geometria euclidiana - Santos, Ednaldo Sena dos (2013)
This work presents a research on problems of maxima and minima of the Euclidean geometry. Initially we present some preliminary results followed by statements that in essence use basic concepts of geometry. Below are some problems of maximizing area and minimizing perimeter of triangles and convex polygons, culminating in a proof of the isoperimetric inequality for polygons and review the general case. Solve some classical problems of geometry that are related to outliers and present other problems as proposed.